2023
DOI: 10.1186/s12967-023-03900-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of large extracellular vesicles (L-EV) derived from human regulatory macrophages (Mreg): novel mediators in wound healing and angiogenesis?

Abstract: Background Large extracellular vesicles (L-EV) with a diameter between 1 and 10 µm are released by various cell types. L-EV contain and transport active molecules which are crucially involved in cell to cell communication. We have shown that secretory products of human regulatory macrophages (Mreg) bear pro-angiogenic potential in-vitro and our recent findings show that Mreg cultures also contain numerous large vesicular structures similar to L-EV with so far unknown characteristics and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Prior research conducted by the authors has been dedicated to characterizing Mreg for several years [ 8 , 12 , 16 ], demonstrating their ability to secrete pro-angiogenic factors, particularly under hypoxic conditions [ 8 ]. Building upon these findings, a GMP-compliant protocol for the production of Mreg was developed and a phase I/II study employing Mreg for treating patients with chronic limb threatening ischemia (CLTI) is under preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research conducted by the authors has been dedicated to characterizing Mreg for several years [ 8 , 12 , 16 ], demonstrating their ability to secrete pro-angiogenic factors, particularly under hypoxic conditions [ 8 ]. Building upon these findings, a GMP-compliant protocol for the production of Mreg was developed and a phase I/II study employing Mreg for treating patients with chronic limb threatening ischemia (CLTI) is under preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Different research groups have demonstrated in recent years that distinct macrophage subtypes can be differentiated in vitro by the administration of various cytokines/ factors (e.g., IL-4, IL-13, IFNγ, LPS), signifying the potential of these in vitro-differentiated cell types in the context of cell therapy [10,11]. We and others have shown that the administration of IFNγ on day 6 of the differentiation period can generate an anti-inflammatory, T-cell suppressive, and potentially pro-angiogenic macrophage subtype known as regulatory macrophages (Mreg) [7,8,[12][13][14][15]. These Mreg cells have already been successfully employed in a clinical study to reduce rejection reactions in kidney transplantations [4,6].…”
Section: Discussionmentioning
confidence: 99%